Illocutionary Speech Acts in Guy de Maupassant’s Short Story A Family - Nuriyah, Rohmah Sinta; Khusain, M. Fadli; Febriani, Ayu Novita; Andini, Andini; Dewi, Ashifah Rahma; Sari, Eny Maulita Purnama (Universitas Pahlawan Tuanku Tambusai, 2026)
The study of illocutionary speech acts is important for understanding implicit meaning in literary texts. However, previous studies on illocutionary speech acts in literary texts tend to emphasize classification rather than contextual interpretation of meaning. This study aims to identify the types of illocutionary speech acts in Guy de Maupassant’s short story “A Family.” The data source was the short story, and the unit of analysis consisted of 22-character utterances selected from the dialogues. A qualitative descriptive method was applied using Searle’s theory of illocutionary acts. The findings show three types of illocutionary acts: assertive, directive, and expressive. Assertive acts were the most dominant, functioning to convey information, reflection, and social evaluation. This dominance indicates that the story emphasizes reflective meaning and indirect social criticism.